Evaluation of a long-term transformational leadership development program - Carolin Abrell; Jens Rowold; Jürgen Weibler; Martina Moenninghoff (Zeitschrift für Personalforschung (ZfP), 2011)
This study represents a multi-method, multi-source, and longitudinal evaluation of a leadership development program in Germany. For the development of transformational leadership, the methods of leadership feedback, training, and coaching were combined into a program. The effects of this program were evaluated at three, six, nine, and twelve months after training. Altogether, 25 leaders participated in the program. The results revealed that transformational leadership (subordinate assessment) improved six months after training and later on. Also, leaders' performance (leaders' supervisor ratings) and Organizational Citizenship Behavior (subordinate assessment) improved over time. – – In dieser Studie wird ein Personalentwicklungsprogramm zur Verbesserung der transformationalen Führungsleistung bei Führungskräften vorgestellt und empirisch evaluiert. Diese Evaluierung erfolgt im Längsschnitt und bedient sich verschiedener Methoden (Führungsstilfeedback, Trainingseinheiten, Coaching) und Perspektiven. Die Trainingseffekte wurden 3, 6, 9 und 12 Monate nach dem Training erfasst. Insgesamt nahmen 25 deutsche Führungskräfte an dem Programm teil. Die Ergebnisse belegen eine Verbesserung in transformationaler Führung (Mitarbeiter-Einschätzung) bereits nach 6 Monaten. Zudem verbesserten sich die Leistung der Führungskräfte (Einschätzung durch Vorgesetzte) und das Organizational Citizenship Behavior (Mitarbeiter- Einschätzung).
Keywords: M10; M53; N28; 330; leadership development; performance; Organizational Citizenship Behavior; personnel development; transformational leadership; Führungskräfteentwicklung; Führungsstil; Arbeitsverhalten; Deutschland